Characteristics of multiple emulsions stabilized by myosin from bighead carp (Aristichthys nobilis) - Yuhe Ma; Jianxiong Hou; Yin Cao; Wuyin Weng; Linfan Shi; Zhongyang Ren (Food Science of Animal Products)
Myosin from bighead carp (Aristichthys nobilis) and span 60 were used to successfully prepare multiple emulsions through a one-step emulsification method. The characteristics of multiple emulsions stabilized by span 60 and myosin from bighead carp were analyzed. The absolute value of the zeta potential of the multiple emulsions increased with the increase of myosin concentration from 0.5 to 4 g/100 mL. Meanwhile, the size of multiple emulsions reduced with the increase of myosin concentration. The optical microscope and laser confocal microscope also verified that the size of multiple emulsions decreased and the emulsion droplets in the emulsion became uniform with the increase of protein concentration. However, the myosin was not enough to cover the oil droplets, and the droplet size increased and aggregation occurred at the concentration of 0.5 g/100 mL. The flocculation index and creaming index showed that increasing protein concentration could enhance the stability of various emulsions stabilized by span 60 and bighead carp myosin and the emulsions were stable for a longer period at 2–4 g/100 mL myosin addition. Furthermore, the stability index of multiple emulsions stabilized by myosin at 4 g/100 mL changed relatively few compared to the others. These results suggest that the emulsion had the best stability when the protein concentration was 4 g/100 mL. These results indicate that bighead carp myosin in conjunction with span 60 could be used as an emulsifier to prepare stable multiple emulsions. This study may be helpful for the development of multiple emulsions constructed using fish proteins.